Nurses' occupational fatigue level and risk factors: A systematic review and meta-analysis. - Rong Pi; Yunfang Liu; Rong Yan; Zong De; Yali Wan; Yi Chen; Zihan He; Fang Liu; Yan Wang; Suyun Li (PLoS ONE)
Background Occupational fatigue, characterized by both physical and mental exhaustion, is a pressing concern in various professions, particularly among nurses. Studies have consistently linked occupational fatigue to decreased productivity, heightened error rates, and compromised decision-making abilities, posing significant risks to both individual nurses and healthcare organizations. Despite its recognized impact, the global prevalence of occupational fatigue among nurses remains incompletely understood, and rigorous evaluations of the multifaceted factors influencing nurses' occupational fatigue are scarce in the existing literature. Objectives This study aims to estimate the pooled score of nurses' occupational fatigue, and to systematically review the factors associated with nurses' occupational fatigue. Methods The review searched eight databases, including PubMed, Web of Science, Scopus, CINAHL, PsycINFO, and Chinese databases such as China National Knowledge Infrastructure (CNKI), Chinese Biological Medical (CBM), and Wan Fang Database. The temporal scope of our search covers the period from the inception of each database to October 1, 2023. The PRISMA guidelines were followed in the reporting of the meta-analysis and systematic review. The meta-analysis was conducted using Stata 18.0 software, employing a random-effects model to pool the mean score and standard deviation of the Occupational Fatigue Exhaustion Recovery (OFER) scale. The restricted maximum-likelihood estimator was utilized to calculate the heterogeneity variance τ². Subgroup analysis was conducted to explore sources of heterogeneity. The registration PROSPERO number is CRD42023456337. Results After a rigorous selection process, 28 articles were ultimately deemed suitable for inclusion in this article, which encompassed a total of 13,290 registered nurses. The pooled mean scores for chronic fatigue, acute fatigue, and inter-shift recovery were 53.24 (95% CI: 48.42-58.28), 64.00 (95% CI: 60.62-67.38), and 47.37 (95% CI: 43.24-51.50), respectively. The subgroup analyses of occupational fatigue among nurses yield crucial insights into the way regional, age, temporal, and departmental factors interact to influence fatigue levels. In addition, the factors affecting nurses' occupational fatigue were found to include cultural, organizational and individual variables. Conclusion A moderately high level of acute and chronic fatigue was observed among nurses, while the level of inter-shift recovery was low to moderate. It is imperative that healthcare systems provide enhanced support for nurses, a multifaceted approach is required, encompassing cultural shifts to reduce the normalization of overwork, organizational reforms to enhance staffing and scheduling, the implementation of fair compensation mechanisms, the development of targeted educational programs and individual-level interventions to promote healthier lifestyle practices.